PENGARUH JARAK TANAM PADA BUDIDAYA RUMPUT LAUT (Eucheuma cottonii) TERHADAP SPESIFIKASI MUTU KARAGINAN - Ismal. Z, Muhammad; Wijaya, Muhammad; Kadirman, Kadirman (Jurnal Pendidikan Teknologi Pertanian, 2018)
The purpose this research was to determine the effect of plant spacing on seaweed the quality specifications of carrageenan. This research uses a Completely Randomized Design (CRD). Randomization was carried out using a random table of 3 treatments, namely a distance of 40 cm and a distance of 60 with a control distance of 20 cm and repeated 3 times. The method used in determining the floor plan / place is the lottery method. Parameters observed included water content, ash content, sulfate content and viscosity. The results showed that the best treatment was found in carrageenan Eucheuma with a spacing of 40 cm, the best quality determinant based on the parameters value of water content (11.49), value of ash conten (21.23), value of sulfate conten (32, 40) and value of viscosity (61).